RETRACTED: Approbation of functional diagnostics methods for application in the plant state assessing - Berestneva Yuliya; Mezhevova Alina (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001